2023
DOI: 10.1021/jacs.3c05632
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic ATRP Depolymerization: Temporal Control at Low ppm of Catalyst Concentration

Kostas Parkatzidis,
Nghia P. Truong,
Krzysztof Matyjaszewski
et al.

Abstract: A photocatalytic ATRP depolymerization is introduced that significantly suppresses the reaction temperature from 170 to 100 °C while enabling temporal regulation. In the presence of low-toxicity iron-based catalysts and under visible light irradiation, near-quantitative monomer recovery could be achieved (up to 90%), albeit with minimal temporal control. By employing ppm concentrations of either FeCl2 or FeCl3, the depolymerization during the dark periods could be completely eliminated, thus enabling temporal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…When light was used for activation in addition to an iron catalyst in a photothermal system, the temperature could be lowered to 100 °C, and almost perfect temporal control was achieved with low catalyst loadings at 120 °C. 152 Once again, the results for the polymers produced by ATRP show that the depolymerization temperature can be lowered signicantly compared to conditions used for FRP (∼300 °C (ref. 127) vs. 100 °C for polymethacrylates) as the activation energy of the initiation step is decreased by the functional end-groups.…”
Section: Thermodynamic Approaches To Solution Depolymerizationmentioning
confidence: 95%
“…When light was used for activation in addition to an iron catalyst in a photothermal system, the temperature could be lowered to 100 °C, and almost perfect temporal control was achieved with low catalyst loadings at 120 °C. 152 Once again, the results for the polymers produced by ATRP show that the depolymerization temperature can be lowered signicantly compared to conditions used for FRP (∼300 °C (ref. 127) vs. 100 °C for polymethacrylates) as the activation energy of the initiation step is decreased by the functional end-groups.…”
Section: Thermodynamic Approaches To Solution Depolymerizationmentioning
confidence: 95%
“…49 Impressively, the Matyjaszewski group was able to significantly boost the depolymerization conversions to 70-80%, by performing reactions at 170 °C and utilizing either a copper or iron-based catalyst. [50][51][52] On the photo-thermal front, our group recently reported that photocatalytic ATRP depolymerization could also be successful under blue light irradiation and iron catalysis, 53 also reaching high monomer recovery (up to 90%). It is noted that the depolymerization of the aforementioned ATRP-made materials can take place in up to 2 M concentration with the exception of a recent report that showcases a higher temperature bulk depolymerization.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that the depolymerization of the aforementioned ATRP-made materials can take place in up to 2 M concentration with the exception of a recent report that showcases a higher temperature bulk depolymerization. 54 However, current literature reports, including both solution and bulk depolymerization strategies, have focused nearly exclusively on chlorine-terminated polymers, 45,[49][50][51][52][53][54] even though the vast majority of polymers prepared by ATRP have a bromine end-group. Therefore, the development of a single-step method to depolymerize bromine-terminated polymers yielding high conversions would significantly expand the scope of materials compatible with chemical recycling.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Current chemical methods for recycling vinyl-derived homopolymers are limited to a few energy-intensive processes, such as heating above a ceiling temperature, [11][12][13][14] pyrolysis, [15] and incineration, [16] which can result in complex product mixtures not suitable for repolymerization. Promising recent studies on catalyzed [17,18] and end-group assisted depolymerization, [19,20] address the highenergy concerns associated with other ceiling temperature schemes, but thus far remain material-specific.…”
Section: Introductionmentioning
confidence: 99%